Job Description Transformation in Cirebon: Adapting Human Resource Needs with Artificial Intelligence - Agus Rohmat Hidayat; Nur Alifah (Sahabat Publikasi, 2026)
The development of artificial intelligence (AI) has raised the urgent need to revise job descriptions in government agencies, especially in Cirebon City. This study examines how the implementation of AI changes the competencies needed in the functional positions of state civil servants (ASN), as well as the necessary HR planning adjustment strategies. Using a systematic literature review approach, the study identifies several key dimensions of transformation, including the shift from purely technical competencies toward human–AI collaboration, the redefinition of workloads in functional positions such as translators and analysts, the increasing role of AI in talent recruitment and development, the emergence of digital output-based performance indicators, and the growing urgency of AI competency development policies in the public sector. The results of the analysis show that job description transformation is not merely an administrative revision, but a strategic restructuring that requires synergy between human resource planning, bureaucratic reform, and well-planned technology adoption. In conclusion, the integration of AI into public sector human resource management necessitates a comprehensive and adaptive redesign of job descriptions to ensure alignment with evolving technological demands. This transformation is essential to enhance organizational effectiveness, improve workforce competencies, and support sustainable bureaucratic performance in the digital era.